A Comparative Analysis of Plot Housing Schemes and MultiStoreyed Apartment Block Housing Schemes in Dhaka: Land Economisation and Urban Community Services in the Context of Post Private Housing Land Development Rule, 2004 Scenario of Bangladesh - Muhammad , Shamsuzzaman (Journal of Bangladesh Institute of Planners, 2014)
In Bangladesh major share of urban land for housing is supplied through spontaneous development and the rest is planned development through government agencies, housing cooperatives and private companies. These developments provide mostly Housing Plots and do not leave enough land for urban community facilities. To ensure minimum quantity of land for urban community facilities in private housing, a law has been enacted in 2004. Though, the ‘Multi-Storeyed Apartment Block Housing Schemes’, inherently capable of freeing up more land for urban community facilities is less used in Bangladesh. A comparative analysis of these two approaches has been done through a design exercise for housing 20,000 people on a hypothetical site for the post Private Housing Land Development Rule 2004 scenario of Bangladesh. It shows that the ‘Multi-Storeyed Apartment Block Housing Schemes’ saves greater amount of valuable urban land that could be utilized for urban community facilities. Journal of Bangladesh Institute of Planners, Vol. 7, Dec 2014, pp. 43-52